1977
DOI: 10.1007/bf02236385
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of adult sheep with reduced doses ofBrucella Melitensis strain rev. 1

Abstract: A trial was made to test the safety of a Brucella melitensis strain Rev. 1 vaccine when used in various doses on pregnant sheep and a control group of pregnant goats. It was found that local sheep were more susceptible than goats to the effects of this vaccine, and that the accepted dosage rate of 10+5 viable organisms, as recommended for adult goats, should not be used on pregnant sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…15,27,28 In comparison to full dose, the reduced dose elicits shorter and less intense antibody response following vaccination [29][30][31] and can be used safely in pregnant sheep and goats. [30][31][32][33][34][35] However, excretion of vaccine strain mainly in vaginal excretion and foetal contents during abortion in pregnant sheep and goats after field infections [36][37][38][39] further showed the necessity to put stress on different methods of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…15,27,28 In comparison to full dose, the reduced dose elicits shorter and less intense antibody response following vaccination [29][30][31] and can be used safely in pregnant sheep and goats. [30][31][32][33][34][35] However, excretion of vaccine strain mainly in vaginal excretion and foetal contents during abortion in pregnant sheep and goats after field infections [36][37][38][39] further showed the necessity to put stress on different methods of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…However, field results obtained after the application of Rev. 1/S19 at reduced doses has led to a divergence of opinions among different experts about its usefulness and implications: many authors have reported a significant number of reproductive failures/vaccine excretion [155][156][157], advising against the use of this strategy in brucellosis control programs. In addition, some authors have showed that this immunization strategy using Rev.…”
Section: Application Of Reduced Doses Of Vaccinementioning
confidence: 99%
“…1/S19 induces an inadequate protection against B. melitensis/B. abortus infection [156][157][158][159]. Additionally, reduced doses may not avoid the induction of persistent antibody titters when Rev.…”
Section: Application Of Reduced Doses Of Vaccinementioning
confidence: 99%